2018
DOI: 10.1111/codi.14473
|View full text |Cite
|
Sign up to set email alerts
|

Assessing surgical difficulty in locally advanced mid–low rectal cancer: the accuracy of two MRI‐based predictive scores

Abstract: Aim Predicting surgical difficulty is a critical factor in the management of locally advanced rectal cancer (LARC). This study evaluates the accuracy and external validity of a recently published morphometric score to predict surgical difficulty and additionally proposes a new score to identify preoperatively LARC patients with a high risk of having a difficult surgery. Methods This is a retrospective study based on the European MRI and Rectal Cancer Surgery (EuMaRCS) database, including patients with mid/low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 50 publications
1
41
0
Order By: Relevance
“…Yamaoka et al . reported that MFA was an independent predictor of surgical difficulty in robotic‐assisted TME [17], while the study from EuMaRCS did not show any influence of MFA on the difficulty of laparoscopic TME [16]. Escal et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yamaoka et al . reported that MFA was an independent predictor of surgical difficulty in robotic‐assisted TME [17], while the study from EuMaRCS did not show any influence of MFA on the difficulty of laparoscopic TME [16]. Escal et al .…”
Section: Discussionmentioning
confidence: 99%
“…Pathological T stage was associated with robotic-assisted ME, following the results of laparoscopic surgery for rectal cancer [12]. The pathological T stage was one of the important factors in the European MRI and Rectal Cancer Surgery (EuMaRCS) scoring system [16]. However, for juxta-anal rectal cancer, the pT stage was not a predictor of difficulty for robotic-assisted ISR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If this applies for a proctoscope, it would be consistent to find a difference also when a flexible or rigid trans-anal platform is placed and used in procedures where dissection is based on geometrical tips (the so-called O and triangle dissection planes) [5] and on a dynamic anatomic distortion made by the pneumorectum [5]. Several authors correlated the anatomical variables with surgical results, for open, robotics, laparoscopic, and TaTME dissections [8,[17][18][19][20][21][22][23][24]. In a small series of patients who underwent open surgery for low rectal tumours, no significant differences were detected between the pelvis depth of females and males.…”
Section: Discussionmentioning
confidence: 92%
“…At the restaging MRI, the lesion showed a moderate response (ymrT2N0). After estimating the European MRI and Rectal Cancer Surgery (EuMaRCS) score for surgical difficulty (2/10) [3], an ‘up‐to‐down’ rectal resection was planned.…”
mentioning
confidence: 99%